PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PASIEN PADA KELAS VIP, 1, 2, DAN 3 (STUDI PADA RSU PKU MUHAMMADIYAH GAMPING YOGYAKARTA) - Virdy Kurniawan; Susanto Susanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2014)
This thesis examines the influence of service quality and price to patient satisfaction at the class VIP, 1, 2, and 3 in RSU PKU Muhammadiyah Unit 2 Gamping Yogyakarta. The issues examined are: there is influence of service quality and price to patient satisfaction simultaneously at class VIP, 1, 2 and class 3 in RSU PKU Muhammadiyah Unit 2 Gamping, there is influence of service quality dimensions to patient satisfaction individually at class VIP, 1, 2 and class 3 in RSU PKU Muhammadiyah Unit 2 Gamping, and there is influence of service prices on patient satisfaction individually at class VIP, 1, 2 and VIP 3 in RSU PKU Muhammadiyah Unit 2 Gamping. This research is quantitative with the cross sectional study such as data collected only once. Data collected using questionnaires. Questionnaires carried out on 160 RSU PKU Muhammadiyah Unit 2 Gamping patients who are derived from the class VIP, class 1, 2, and class 3. Respondents determined by using convenience sampling who have stayed at PU Muhammadiyah Hospital Unit 2 Gamping at least 1 day. From the study, it is found that there is significant effect of service quality and price simultaneously on patient satisfaction at class VIP, 1, 2 and 3 in RSU PKU Muhammadiyah Unit 2 Gamping. It is known from the results of the F test which is getting significant results for all classes at µ (0,05). This means that hypothesis 1 proved (There is the influence of service quality and cost simultaneously on patient satisfaction at class VIP, 1, 2 and 3 in RSU PKU Muhammadiyah Unit 2 Gamping). There is significant influence of dimensions of service quality individually to patient satisfaction at class VIP, 1 , 2 and 3 in RSU PKU Muhammadiyah Unit 2 Gamping. It is known from the results of the F test which is getting significant results for all classes at µ (0,05). This means that hypothesis 2 proved (There is the influence of the dimensions of service quality individually on patient satisfaction at class VIP, 1, 2 and 3 in RSU PKU Muhammadiyah Unit 2 Gamping). In this case dimension that has a significant influence on the VIP is tangibles dimension, responsiveness and empathy (the most dominant is empathy). Dimensions that have a significant influence on the class 1 is responsiveness dimension and empathy (the most dominant is empathy). Dimensions that have a significant influence on the class 2 is all dimensions (the most dominant is reliability). Dimensions that have a significant influence on the class 3 is assurance dimension (the most dominant is assurance). There is significant influence of price to patient satisfaction individually at class VIP, 2 and 3 in RSU PKU Muhammadiyah Unit 2 Gamping, except in patients class 1. It is known from the t test at µ (0,05).